Legal Certainty Of Regional Taxes in the Framework of Fiscal Decentralization - Riyo Pramato (Sean Institute, 2026)
This study examines legal certainty in the implementation of local taxes within the framework of fiscal decentralization in Indonesia. Fiscal decentralization is intended to strengthen regional financial autonomy and improve public service quality; however, its implementation still faces challenges such as fiscal disparities and regulatory disharmony. The research employs a normative juridical method using statutory and conceptual approaches, analyzing both primary and secondary legal materials. The findings indicate that Law No. 1 of 2022 has enhanced local taxing authority and promoted policy harmonization, yet its application remains suboptimal due to limited regional capacity and inconsistent norms. Regulatory harmonization, tax system digitalization, and strengthened coordination between central and local governments are essential to ensure legal certainty.